Cure-dependent thermo-chemical modelling and analysis of the manufacturing process of an aircraft composite frame. (April 2015) - Brauner, Christian; Soprano, Pedro; Herrmann, Axel S; Meiners, Dieter
This study contributes to the understanding of the mechanism behind thermo chemical aspects related to the resin transfer moulding manufacturing process of a composite part. The aim is to comprehend the phenomena, to identify related parameters and to get knowledge-based methods for the process development. Therefore, the first part of this study is an experimental study about the behaviour of material properties during the manufacturing process of the single component and the composite. It concludes with constitutive equations for single-process parameters and their associated homogenisation approach for the composite properties. During the manufacturing process, material values of the matrix are changing and influenced by a high number of effects. In the second part, a simulation strategy is been derived. This developed material model integrates a dependency of the time–temperature–polymerisation and fibre volume content. The model is validated in a test case of a manufacturing process of an aircraft component, a fuselage frame.